STATUS GIZI ANAK USIA BALITA PADA KELUARGA SADAR GIZI (KADARZI) DAN NON KADARZI DI DESA SUKOJEMBER KECAMATAN JELBUK KABUPATEN JEMBER - Sulistiyani, Sulistiyani; Zulkarnain, Elfian; Amaliyah, Rizky (IKESMA, 2008)
Nutrition problem is one of the determinant of human resource quality. One of the strategy in conquering the nutrition problem is Kadarzi program. The purpose of this research is to analyze the difference of nutrition status of child under five years old at Kadarzi and non Kadarzi. Research design is analytic observational and based on the time was cross sectional. The number of samples were 101 samples, consisted of 38 Kadarzi and 63 non Kadarzi. The data which had been obtained were analyzed statistically by using Mann-Whitneyâs test, with Î±=0,05. The result of research showed that there was no significantly difference on the fatherâs educational level (p=0.397), familyâs income (p=0.106), TB/U nutrition status index (p=0.369) and BB/TB nutrition status index (p=0.051). The result with Mann-Whitneyâs test showed that there was significantly difference on the motherâs educational level (p=0.024), familyâs nutrition knowledge (p=0.003), energy consumption (p=0.023), protein consumption (p=0.033), BB/U nutrition status index (p=0.016) and combined nutrition status index (p=0.029). Continual nutrition counseling for family, especially non Kadarzi was needed to improve nutrition knowledge. Keywords : nutrition status, child under five years old, keluarga sadar gizi (Kadarzi)